Zakah and Re-distributive Justice in Islam - Ahmad, A. U. F.; Hassan, M. K.; Muhammad Shahed, A. K.E (Universiti Sains Islam Malaysia, 2024)
The Islamic framework within which this study examines is the role of Zakah in redistributive justice. To this end, the following relevant topics were aimed to cover. First, "redistributive justice" is conceptualized. Second, to ground this concept the Islamic viewpoints towards redistribution are highlighted followed by a short discussion on prominent schools of thought in political philosophy of redistributing income. Third , important features of the Islamic strategy for the realisation of the desired pattern of distribution are traced. Fourth, the core topic of the study is elaborated in which the analysis relies on tentative results from an empirical study on how much would be the yield of Zakah in modern economy if it was paid on all kinds of assets liable to it. Finally, an attempt is made to establish one of the pertinent conclusions of this study i.e. how Zakah being a collection of redistributive measures can play an important role in an Islamic economy.